Roof Response to Icing Conditions - Lane,Jean W; Marshall,Stephen J; Munis,Richard H (1979)
Six test roofs of two different slopes - 16.3 deg and 39.8 deg, and three different roof coverings - asphalt shingles, cedar shingles, and corrugated aluminum sheeting, were constructed at USACRREL, Hanover, New Hampshire, and were instrumented with thermocouples, heat flow meters, and calibrated gutters. Measurements were recorded for the winters of 1971-72 and 1972-73. The degree of icing and the chronological changes in the snow cover were recorded on 35-mm Kodachrome slides. It was found that eave icing is a sensitive function of the slope, roof covering composition, and solar radiation. The effects of wind were not investigated; the data were screened to remove all information corresponding to windspeeds over 8 km/h. In order of increasing tendency to form ice dams on the eaves, the roofs were high-slope asphalt, high-slope cedar, high-slope aluminum, low-slope asphalt, low-slope cedar, and low-slope aluminum. (Author)